Rethinking the Ecosystem Functions of Dicranopteris, a Widespread Genus of Ferns - Yang, Long; Huang, Yuhui; Lima, Lucas Vieira; Sun, Zhongyu; Liu, Meijie; Wang, Jun; Liu, Nan; Ren, Hai (Frontiers in Plant Science, 2021)
Dicranopteris is an ancient and widespread genus of ferns in tropical and subtropical regions. The members of this genus always form single-species dominant communities and are common and key species in tropical and subtropical ecosystems. However, they are always cut or burned as part of forest management because they form dense thickets that are thought to interfere with forest regeneration and succession. In the current review, we consider how Dicranopteris species are able to rapidly colonize barren areas and may contribute to ecosystem recovery, resistance to environmental stress, and succession control. Rapid colonization involves prolific spore production, rapid clonal growth, the generation of high surface cover, and the ability to fill gaps; stress resistance includes resistance to abiotic stress and the ability to reduce soil erosion from rainfall, alien species invasion, and soil contamination and toxicity; and succession control includes carbon and nutrient sequestration in soil, moderation of the microclimate, alteration of the soil microbial and faunal communities, and the determination of which other plant species are able to establish in the next successional stage. All of these ecosystem functions may contribute to ecosystem resilience. We also predict that the distribution of Dicranopterisis will increase in response to global warming, changes in precipitation patterns, and increases in soil pollution, deforestation, and land degradation. We suggest that Dicranopteris, as a pioneer fern in forest succession, is a valuable component of tropical and subtropical forests that warrants more attention of researchers and more knowledgeable management by foresters.